Evaluation of Different Biochemical and Hematological Parameters in Different Body Mass Index of Age Groups of Combined Oral Contraceptive Users - Sher, Nabila; Zafar, Hafsa; Tariq, Kalsoom (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective To determine the effect of combined oral contraceptive pills (COC) on the childbearing age group’s lipid profile, blood pressure, and body mass index. Methodology This analytical cross-sectional study was carried out in the Family Planning Department of Peshawar’s tertiary hospital from January to December 2011 on 204 subjects of childbearing women. They are divided into 3 groups (group A 14-25 years, group B 26-36 years, group C 37-49 years), 102 subjects used COC, and a control group of 102 subjects randomly. The goal of the current study was to show how COC affected serum lipid profiles, haemoglobin levels, BMI, and blood pressure. Computer software SPPS version 21 was used to analyse the data. Results Significantly higher levels of these biochemical parameters were measured in oral contraceptive users to confirm the impact of age on these various parameters, including VLDL, Triglycerides, and systolic BP were noted in all three age groups of treated groups. When compared to the control group, all parameters were higher in the group C of COC users, cholesterol by (p<0.0027), HDL by (p<0.031), LDL by (p<0.051), VLDL by (p<0.0001), triglyceride by (p<0.0001), fasting blood sugar by (p<0.00043), BMI by (p<0.0004), systolic BP by (p<0.01) and Hb by (p<0.003). Conclusions Our research demonstrated that combined oral contraceptives use causes changes in lipid profile, body mass index, and blood pressure. The metabolic risk factors associated with these increased values may result in cardiovascular illnesses.